UTILIZACIÓN DE HERRAMIENTAS ESTADÍSTICAS PARA EL PROCESAMIENTO DE DATOS DE CAMPO Y LABORATORIO EN MECÁNICA DE ROCAS, CON APLICACIÓN AL SITIO DOS MONTAÑAS, SIQUIRRES, COSTA RICA - Mora Ch., Rolando (2011)
This paper deals with the classification of the rocks of Dos Montañas, using a modification ofDeere & Miller methodology, and with the application of statistic tools to define the confidence intervals of thedata. The same type of analysis has been performed to study the results of rigid plate and Goodman jack tests.